High-strength low-adsorption high-silicon ceramic tea container and preparation method thereof
By using specific ratio oxide raw materials and additives in ceramic tea ware, the problems of high water absorption and insufficient strength in traditional pottery are solved, and the ceramic tea ware body with high strength and low adsorption performance are achieved, which is suitable for practical utensils such as tea ware.
Patent Information
- Application Number
- CN202411974171.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
AI Technical Summary
During use, traditional high-silicon pottery is prone to damage and discoloration due to high water absorption and insufficient strength. The porous structure causes moisture absorption and expansion to affect the bonding performance of the glaze.
The raw materials such as silica, alumina, barium oxide, zinc oxide and zirconia are used to form a ceramic teaware blank with high strength and low adsorption properties through specific proportioning and sintering processes, and additives such as sodium humate, sodium lignin sulfonate, starch and CMC are added to the blank to improve the strength and stability of the blank.
It achieves high strength and low adsorption properties of ceramic blanks, with water absorption rate ≤3.0%, flexural strength ≥100MPa, and high thermal stability, and is suitable for practical utensils such as tea utensils.
Smart Images

Figure BDA0005220053850000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and particularly relates to a high-strength, low-adsorption, high-silicon ceramic tea set and a preparation method thereof. Background Art
[0002] Pottery is mostly made of clay or high-silica components. The body structure is relatively loose and the density is poor. It usually has a certain water absorption rate, a rough and matte cross-section, no light transmittance, and a rough sound when knocked. Although the material strength is not high, due to its porous structure characteristics, when it is used in practical utensils such as tea sets, it will improve the taste of tea soup and keep the overnight tea from changing its taste. While maintaining the porous air permeability of pottery, some adverse effects will also be encountered during the use of pottery tea sets. For example, at the unglazed rim, due to its porous adsorption effect, it will gradually change color and deepen with the accumulation of tea immersion over time, and finally form a black mark, affecting the user's experience. At the same time, under the water absorption and penetration of the porous body, the phenomenon of hygroscopic expansion occurs, which will further affect the bonding performance of the body and glaze. Some products will form cracking and cracking problems in the later stage.
[0003] The Chinese patent application with application number CN201811140307.6 discloses a high-silicon ceramic with quartz as the matrix material and a preparation method. The weight content of silicon dioxide in the product is 84-88%, the weight content of aluminum oxide is 7-11%, the weight content of potassium oxide is 3-3.5%, the weight content of sodium oxide is 0.5-1.0%, the weight content of calcium oxide is 0.3-0.4%, the weight content of iron oxide is less than 0.07-0.11%, and the weight content of magnesium oxide is 0.2-0.3%; the density of the high-silicon ceramic with quartz as the matrix material is 2.5-2.55g / cm 3 , the flexural strength is 120-140Mpa, and the whiteness of the porcelain body is not less than 80; this invention improves the thermal stability of ceramic products, but in the traditional pottery production process, the high-siliceous body has insufficient strength and strong adsorption, which leads to the pottery's high water absorption rate after high-temperature glaze firing and low product lightness, which in turn leads to problems of easy breakage and discoloration during use. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a high-strength, low-adsorption, high-silicon ceramic tea utensil and a preparation method thereof, which can achieve high strength and low adsorption performance of the ceramic body.
[0005] The technical solution of the present invention is as follows:
[0006] One of the purposes of the present invention is to provide a high-strength, low-adsorption, high-silicon ceramic tea set, the body of which is composed of the following raw materials in parts by weight: 70-72 parts of silicon dioxide, 20-25 parts of aluminum oxide, 1.3-1.8 parts of potassium oxide, 0.8-1.0 parts of sodium oxide, 0.2-0.4 parts of calcium oxide, 0.1-0.2 parts of magnesium oxide, 0.5-1.0 parts of barium oxide, 0.5-2.0 parts of zinc oxide, and 1.0-3.0 parts of zirconium oxide.
[0007] Furthermore, the raw materials of the green body also include additives, and the additives include sodium humate, sodium lignin sulfonate, starch and CMC.
[0008] Furthermore, the sodium humate accounts for 0.3-0.5‰ of the total raw materials, the sodium lignin sulfonate accounts for 0.05-0.15‰ of the total raw materials, the starch accounts for 0.05-0.1‰ of the total raw materials, and the CMC accounts for 0.05-0.15‰ of the total raw materials.
[0009] Furthermore, the raw material of the green body also includes PC67 diluent.
[0010] Furthermore, the PC67 diluent accounts for 2-3‰ of the total raw materials.
[0011] The second object of the present invention is to provide a method for preparing a high-strength, low-absorption, high-silica ceramic tea set, comprising the following steps:
[0012] S1: Weigh silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, barium oxide, zinc oxide, zirconium oxide and additives according to a set ratio, add water and perform ball milling to obtain a slurry;
[0013] S2: adding PC67 diluent to the mud obtained in step S1, stirring evenly, making a green body by slip casting, and obtaining a bisque green body after drying, washing and bisque firing;
[0014] S3: applying matte black glaze to the surface of the bisque-fired body obtained in step S2 by spraying, and drying the body, wherein the thickness of the glaze layer is controlled to be 0.3-0.5 mm;
[0015] S4: putting the green body dried in step S3 into a kiln for sintering, the sintering cycle is 6-9 hours, the maximum sintering temperature is 1230-1250°C, and naturally cooling after sintering to obtain the high-strength, low-adsorption, high-silicon ceramic teaware.
[0016] Furthermore, in step S1, during the ball milling process, the ratio of material: ball: water is 1:2:0.4, the rotation speed of the ball mill is 60 r / min, and the ball milling time is 12 h.
[0017] Furthermore, in step S1, the particle size D50 of the mud material is 0.6-0.85 μm, and the mud specific gravity is 1.75-1.80 g / cm 3 .
[0018] Furthermore, in step S2, after adding the diluent PC67 and stirring, the flowability of 100 mL of mud is: the flow rate is 70-85s after standing for 30 seconds, and the thickening coefficient is 1.3-1.5.
[0019] Furthermore, in step S2, the thickness of the obtained green body is 5-8 mm.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention provides a high-strength, low-adsorption, high-silicon ceramic tea set, which uses aluminum oxide, barium oxide, zinc oxide and zirconium oxide, wherein aluminum oxide can react with silicon dioxide during sintering to form mullite Al2O3·2SiO2, and form a K2O-Al2O3-SiO2 ternary phase diagram system. The lowest eutectic point is the K2O-Al2O3-SiO2 ternary system, in which the three oxides form the lowest eutectic temperature according to a certain ratio. The SiO2 content in the present invention is high, and by adding aluminum oxide to adjust the ratio, it can be closer to the lowest eutectic point, thereby saving energy and reducing its thermal stress. The addition of zirconium oxide is conducive to the transformation of the unstable tetragonal phase of zirconium oxide to the monoclinic phase. The volume expansion of the phase change region forms compressive stress in the material, inhibits the expansion of cracks, and achieves the requirement of enhanced toughness. Zinc oxide and barium oxide can reduce the lowest eutectic point. At the same time, the reversible change between the tetragonal and monoclinic zirconia will produce a volume effect, which will cause cracks to appear when the product containing zirconia is fired. The present invention forms a cubic solid solution with zirconia at high temperature by adding barium oxide. The solid solution maintains an inherent structure in a wide composition range and temperature range, does not undergo crystal transformation, and has no volume change, thereby improving the stability of zirconia and increasing the impact strength of the finished ceramic product. The present invention can also improve the solubility and dispersibility of each component, and achieve precise control of the water absorption rate of the ceramic body, so that its water absorption rate is ≤3.0%. At the same time, the product strength after high-temperature glaze firing is improved, and the thermal stability of the body is relatively high, and it can adapt to water heat exchange at 180°C to 20°C, and is suitable for tea utensils.
[0022] 2. In the present invention, sodium humate, sodium lignin sulfonate, starch and CMC are used as additives to enhance the ceramic teaware blank. Among them, the molecules of sodium humate contain functional groups such as -COO- and -OH, which can form electrovalent bonds or coordination bonds with the positive charge sites on the clay surface. At the same time, the OH bonds in humic acid can form hydrogen bonds with -OH on the clay surface, thereby producing adsorption. In addition, aliphatic hydrocarbon groups such as CH in humic acid can also produce physical adsorption with the clay surface. These adsorptions reduce the distance between clay particles and increase the ability to move freely, thereby improving the plasticity and plasticity of ceramic mud. Starch and CMC have linear polymer structures. After adding water, the hydrophilic groups -OH and -COO- therein combine with water, and the molecules form a network structure through van der Waals bonds and hydrogen bonds, which plays a bonding role. Sodium lignin sulfonate is a long-chain organic polymer compound that can bridge between blank particles to produce a cross-linked irregular network structure, tightly wrapping the blank particles. At the same time, there are many single bonds that can rotate internally in its long molecular chain, and the single bonds make the polymer chain have strong flexibility and elasticity, thereby increasing the strength of the green body. Therefore, the present invention greatly improves the strength of the green body by adding sodium humate, sodium lignin sulfonate, starch and CMC, and the additives of the present invention will not affect the performance of the clay material and the color change after firing.
[0023] 3. In the present invention, PC67 diluent is used to control the thickening coefficient of the green body within 1.3-1.5. The thickening coefficient of the ceramic grouting mud is within this range. After the mud is left to stand, the fluidity and thixotropy are more conducive to production.
[0024] 4. The present invention provides a method for preparing a high-strength, low-adsorption, high-silicon ceramic tea utensil. By controlling the raw material ratio, particle size and grinding time in the formula, the particle size distribution of the raw materials is accurately controlled, thereby improving the overall strength and stability of the green body, reducing the occurrence of green body cracks, and solving the problem of insufficient green body strength in traditional pottery production. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with preferred embodiments. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein; the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can be obtained from commercial channels; the experimental methods in the following embodiments, unless otherwise specified, are all conventional methods.
[0026] Example 1
[0027] The present embodiment provides a high-strength, low-adsorption, high-silicon ceramic tea set, the body of which is composed of the following raw materials in parts by weight: 71 parts of silicon dioxide, 23 parts of aluminum oxide, 1.3 parts of potassium oxide, 0.9 parts of sodium oxide, 0.3 parts of calcium oxide, 0.1 parts of magnesium oxide, 0.5 parts of barium oxide, 2.0 parts of zinc oxide, and 3.0 parts of zirconium oxide.
[0028] In this embodiment, the raw materials of the blank also include additives, and the additives include sodium humate, sodium lignin sulfonate, starch and CMC, wherein the sodium humate accounts for 0.35‰ of the total raw materials, the sodium lignin sulfonate accounts for 0.05‰ of the total raw materials, the starch accounts for 0.1‰ of the total raw materials, and the CMC accounts for 0.12‰ of the total raw materials.
[0029] In this embodiment, the raw materials of the green body also include PC67 diluent, and the proportion of the PC67 diluent is 2.5‰ of the total raw materials.
[0030] This embodiment also provides a method for preparing a high-strength, low-adsorption, high-silica ceramic tea set, comprising the following steps:
[0031] S1: Weigh silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, barium oxide, zinc oxide, zirconium oxide and additives according to a set ratio, add water and perform ball milling to obtain a slurry;
[0032] In this embodiment, the particle size D50 of the mud material is 0.70 μm, and the mud specific gravity is 1.78 g / cm 3 ; During the ball milling process, material: ball: water = 1:2:0.4, the speed of the ball mill is 60r / min, and the ball milling time is 12h;
[0033] S2: adding PC67 diluent to the mud obtained in step S1, stirring evenly, making a green body by slip casting, and obtaining a bisque green body after drying, washing and bisque firing;
[0034] S3: applying matte black glaze to the surface of the bisque-fired body obtained in step S2 by spraying, and drying the body, wherein the thickness of the glaze layer is controlled to be 0.3-0.5 mm;
[0035] In this embodiment, the thickness of the obtained green body is 8 mm; the flowability of 100 mL of mud after adding the diluent PC67 and stirring is: the flow rate is 70-85 s after standing for 30 s, and the thickening coefficient is 1.5;
[0036] S4: putting the green body after drying in step S3 into a kiln for sintering, the sintering cycle is 9 hours, the maximum sintering temperature is 1240°C, and naturally cooling after sintering to obtain the high-strength, low-adsorption, high-silicon ceramic teaware.
[0037] Example 2
[0038] The present embodiment provides a high-strength, low-adsorption, high-silicon ceramic tea set, the body of which is composed of the following raw materials in parts by weight: 72 parts of silicon dioxide, 25 parts of aluminum oxide, 1.5 parts of potassium oxide, 0.8 parts of sodium oxide, 0.2 parts of calcium oxide, 0.15 parts of magnesium oxide, 0.7 parts of barium oxide, 0.5 parts of zinc oxide, and 2.0 parts of zirconium oxide.
[0039] In this embodiment, the raw materials of the green body also include additives, which include sodium humate, sodium lignin sulfonate, starch and CMC, wherein the sodium humate accounts for 0.4‰ of the total raw materials, the sodium lignin sulfonate accounts for 0.12‰ of the total raw materials, the starch accounts for 0.05‰ of the total raw materials, and the CMC accounts for 0.05‰ of the total raw materials.
[0040] In this embodiment, the raw materials of the green body also include PC67 diluent, and the proportion of the PC67 diluent is 2‰ of the total raw materials.
[0041] This embodiment also provides a method for preparing a high-strength, low-adsorption, high-silica ceramic tea set, comprising the following steps:
[0042] S1: Weigh silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, barium oxide, zinc oxide, zirconium oxide and additives according to a set ratio, add water and perform ball milling to obtain a slurry;
[0043] In this embodiment, the particle size D50 of the mud material is 0.6 μm, and the mud specific gravity is 1.75 g / cm 3 ; During the ball milling process, material: ball: water = 1:2:0.4, the speed of the ball mill is 60r / min, and the ball milling time is 12h;
[0044] S2: adding PC67 diluent to the mud obtained in step S1, stirring evenly, making a green body by slip casting, and obtaining a bisque green body after drying, washing and bisque firing;
[0045] S3: applying matte black glaze to the surface of the bisque-fired body obtained in step S2 by spraying, and drying the body, wherein the thickness of the glaze layer is controlled to be 0.3-0.5 mm;
[0046] In this embodiment, the thickness of the obtained green body is 7 mm; the flowability of 100 mL of mud after adding the diluent PC67 and stirring is: the flow rate is 70-85 s after standing for 30 s, and the thickening coefficient is 1.4;
[0047] S4: putting the green body dried in step S3 into a kiln for sintering, with a firing cycle of 6 hours and a maximum sintering temperature of 1250°C. After the firing is completed, the green body is naturally cooled to obtain the high-strength, low-adsorption, high-silicon ceramic teaware.
[0048] Example 3
[0049] The present embodiment provides a high-strength, low-adsorption, high-silicon ceramic tea set, the body of which is composed of the following raw materials in parts by weight: 70 parts of silicon dioxide, 20 parts of aluminum oxide, 1.8 parts of potassium oxide, 1.0 parts of sodium oxide, 0.4 parts of calcium oxide, 0.2 parts of magnesium oxide, 1.0 parts of barium oxide, 1.2 parts of zinc oxide, and 1.0 parts of zirconium oxide.
[0050] In this embodiment, the raw materials of the green body also include additives, and the additives include sodium humate, sodium lignin sulfonate, starch and CMC, wherein the sodium humate accounts for 0.5‰ of the total raw materials, the sodium lignin sulfonate accounts for 0.15‰ of the total raw materials, the starch accounts for 0.08‰ of the total raw materials, and the CMC accounts for 0.15‰ of the total raw materials.
[0051] In this embodiment, the raw materials of the green body also include PC67 diluent, and the proportion of the PC67 diluent is 3‰ of the total raw materials.
[0052] This embodiment also provides a method for preparing a high-strength, low-adsorption, high-silica ceramic tea set, comprising the following steps:
[0053] S1: Weigh silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, barium oxide, zinc oxide, zirconium oxide and additives according to a set ratio, add water and perform ball milling to obtain a slurry;
[0054] In this embodiment, the particle size D50 of the mud material is 0.85 μm, and the mud specific gravity is 1.80 g / cm 3 ; During the ball milling process, material: ball: water = 1:2:0.4, the speed of the ball mill is 60r / min, and the ball milling time is 12h;
[0055] S2: adding PC67 diluent to the mud obtained in step S1, stirring evenly, making a green body by slip casting, and obtaining a bisque green body after drying, washing and bisque firing;
[0056] S3: applying matte black glaze to the surface of the bisque-fired body obtained in step S2 by spraying, and drying the body, wherein the thickness of the glaze layer is controlled to be 0.3-0.5 mm;
[0057] In this embodiment, the thickness of the obtained green body is 5 mm; the flowability of 100 mL of mud after adding the diluent PC67 and stirring is: the flow rate is 70-85 s after standing for 30 s, and the thickening coefficient is 1.3;
[0058] S4: putting the green body after drying in step S3 into a kiln for sintering, the sintering cycle is 7.5 hours, the maximum sintering temperature is 1230°C, and naturally cooling after sintering to obtain the high-strength, low-adsorption, high-silicon ceramic teaware.
[0059] Example 4
[0060] It is basically the same as Example 1, except that no additive is included in this example.
[0061] Example 5
[0062] The method is substantially the same as Example 1, except that the additive in this example does not contain starch and CMC.
[0063] Example 6
[0064] The method is basically the same as Example 1, except that in step S1 of the preparation method of this embodiment, the particle size D50 of the mud material is 0.90 μm, and the mud specific gravity is 1.72 g / cm 3 .After adding the diluent PC67 and stirring, the flow properties of 100mL mud are: the flow rate is 38s after standing for 30 seconds, and the thickening coefficient is 1.05.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that the teaware of this comparative example is composed of the following raw materials in parts by weight: 68 parts of silicon dioxide, 26 parts of aluminum oxide, 1.9 parts of potassium oxide, 1.2 parts of sodium oxide, 0.3 parts of calcium oxide, 0.5 parts of magnesium oxide, 1.1 parts of barium oxide, 2.5 parts of zinc oxide, and 4 parts of zirconium oxide.
[0067] Comparative Example 2
[0068] The difference from Example 1 is that the body of the tea utensil of this comparative example is composed of the following raw materials in parts by weight: 73 parts of silicon dioxide, 19 parts of aluminum oxide, 2.0 parts of potassium oxide, 1.1 parts of sodium oxide, 0.2 parts of calcium oxide, 0.5 parts of magnesium oxide, 0.2 parts of barium oxide, 0.4 parts of zinc oxide, and 0.8 parts of zirconium oxide.
[0069] Comparative Example 3
[0070] The difference from Example 1 is that in step S4 of the preparation method of the teaware of this comparative example, the firing cycle is 6 hours and the maximum sintering temperature is 1280°C.
[0071] Implementation effect evaluation
[0072] The following is a specific test of the tea sets prepared in Examples 1-6 and Comparative Examples 1-3 to further illustrate the excellent effects achieved by the present invention.
[0073] Adsorption test: The teaware blanks prepared in Examples 1-6 and Comparative Examples 1-3 were taken out from the soaked tea liquid, washed, and dried naturally for 7 days, and compared with the samples not soaked in tea liquid to observe the color change of the unglazed part. The ones with no color change were determined to have low adsorption, and the ones with darker color and tea stains adsorbed were determined to have high adsorption and unqualified products.
[0074] The test results are shown in the table below:
[0075] Table 1 Statistical table of ceramic tea set performance test results
[0076]
[0077] From the data in the above table, it can be seen that the ceramic teaware prepared in Examples 1-3 has a flexural strength of >100 MPa, which is relatively high; the water absorption rate is <3.0%, and the adsorption is low. Thermal stability test of the product: it is not cracked after three water heat exchanges at 180-20°C, which is qualified.
[0078] By comparing the experimental data of Examples 4 and 5 with that of Example 1, it can be seen that the flexural strength of the ceramic tea utensils prepared in Examples 4 and 5 is less than 100 MPa, and the flexural strength of Examples 4 and 5 is worse than that of Example 1 due to the lack of or small amount of additives; their water absorption rates are all greater than 3.0%, and their adsorption is relatively low.
[0079] By comparing the experimental data of Example 6 with that of Example 1, it can be seen that the flexural strength of the ceramic teaware prepared in Example 6 is less than 100 MPa. The different processing methods of the formula and the high particle size D50 result in a significant decrease in the flexural strength compared with Example 1; the water absorption rate is less than 3.0%, and the adsorption capacity is relatively low.
[0080] By comparing the experimental data of Examples 1 and 2 with Example 1, it can be seen that when the formula composition deviates from the composition of the present invention, the flexural strength of the ceramic teaware is less than 100 MPa, and the flexural strength is poor; the water absorption rate is greater than 3.0%, and the adsorption is good. Thermal stability test of the sample: cracking occurs once in the water heat exchange at 180-20℃, and all are unqualified.
[0081] By comparing the experimental data of comparative example 3 with that of example 1, it can be seen that when the firing temperature is increased, the flexural strength of the teaware is less than 100 MPa, which is poor; the water absorption rate is less than 0.5%, and although the adsorption is poor, it has been vitrified and does not belong to the scope of tea pottery. The thermal stability test of the sample: cracking occurs once in the water heat exchange at 180-20℃, and all are unqualified.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A high-strength, low-adsorption, high-silica ceramic tea set, characterized in that: The body of the ceramic tea set is composed of the following raw materials in parts by weight: 70-72 parts of silicon dioxide, 20-25 parts of aluminum oxide, 1.3-1.8 parts of potassium oxide, 0.8-1.0 parts of sodium oxide, 0.2-0.4 parts of calcium oxide, 0.1-0.2 parts of magnesium oxide, 0.5-1.0 parts of barium oxide, 0.5-2.0 parts of zinc oxide, and 1.0-3.0 parts of zirconium oxide.
2. A high-strength, low-absorption, high-silica ceramic tea set according to claim 1, characterized in that: The raw materials of the green body also include additives, and the additives include sodium humate, sodium lignin sulfonate, starch and CMC.
3. A high-strength, low-absorption, high-silica ceramic tea set according to claim 2, characterized in that: The sodium humate accounts for 0.3-0.5‰ of the total raw materials, the sodium lignin sulfonate accounts for 0.05-0.15‰ of the total raw materials, the starch accounts for 0.05-0.1‰ of the total raw materials, and the CMC accounts for 0.05-0.15‰ of the total raw materials.
4. A high-strength, low-absorption, high-silicon ceramic tea set according to claim 3, characterized in that: The raw materials of the green body also include PC67 diluent.
5. The high-strength, low-absorption, high-silicon ceramic tea set according to claim 4, characterized in that: The PC67 diluent accounts for 2-3‰ of the total raw materials.
6. The method for preparing a high-strength, low-adsorption, high-silica ceramic tea utensil according to claim 5, characterized in that: The following steps are involved: S1: Weigh silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, barium oxide, zinc oxide, zirconium oxide and additives according to a set ratio, add water and perform ball milling to obtain a slurry; S2: adding PC67 diluent to the mud obtained in step S1, stirring evenly, making a green body by slip casting, and obtaining a bisque green body after drying, washing and bisque firing; S3: applying matte black glaze to the surface of the bisque-fired body obtained in step S2 by spraying, and drying the body, wherein the thickness of the glaze layer is controlled to be 0.3-0.5 mm; S4: putting the green body dried in step S3 into a kiln for sintering, the sintering cycle is 6-9 hours, the maximum sintering temperature is 1230-1250°C, and naturally cooling after sintering to obtain the high-strength, low-adsorption, high-silicon ceramic teaware.
7. The method for preparing a high-strength, low-adsorption, high-silica ceramic teaware according to claim 6, characterized in that: In step S1, during the ball milling process, the ratio of material: ball: water is 1:2:0.4, the rotation speed of the ball mill is 60 r / min, and the ball milling time is 12 h.
8. The method for preparing a high-strength, low-adsorption, high-silica ceramic tea utensil according to claim 6, characterized in that: In step S1, the particle size D50 of the mud material is 0.6-0.85 μm, and the mud specific gravity is 1.75-1.80 g / cm 3 .
9. The method for preparing a high-strength, low-absorption, high-silica ceramic tea utensil according to claim 6, characterized in that: In step S2, after adding the diluent PC67 and stirring, the flowability of 100 mL of the mud is as follows: the flow rate is 70-85 s after standing for 30 s, and the thickening coefficient is 1.3-1.
5.
10. The method for preparing a high-strength, low-adsorption, high-silica ceramic tea utensil according to claim 6, characterized in that: In step S2, the thickness of the obtained green body is 5-8 mm.
Citation Information
Patent Citations
High-silicon ceramic with quartz as base material and preparation method
CN109095907A